Fibroblast growth factor-23 but not sKlotho levels are related to diastolic dysfunction in type 1 diabetic patients with early diabetic nephropathy - ARIKAN, İZZET HAKKI (SPRINGER, 2016)
To investigate the soluble Klotho (sKlotho) and fibroblast growth factor-23 (FGF-23) levels and echocardiographic findings in type 1 diabetic patients with no or early diabetic nephropathy. A total of 147 subjects (mean age 34.1 +/- A 9.2 years, 55.8 % were females) including type 1 diabetic patients with glomerular filtration rate (GFR) > 60 ml/min (n = 71, mean age 34.3 +/- A 9.5 years, 54.9 % were females) and healthy controls (n = 76, mean age 33.9 +/- A 9.1 years, 56.6 % were females) were included in this study. Data on demographic characteristics, blood biochemistry, urinalysis, diabetes-related complications and echocardiography were recorded. Serum levels for sKlotho and FGF-23 were determined by ELISA method. Patient and control groups were similar in terms of mean sKlotho (509.2 +/- A 183.5 and 547.6 +/- A 424.0 pg/ml, respectively) and FGF-23 (76.2 +/- A 15.6 and 77.2 +/- A 15.1 pg/ml, respectively) levels as well as echocardiographic findings. No significant correlation of sKlotho (pg/ml) and FGF-23 (pg/ml) levels with cardiac parameters was noted among diabetic patients. In subgroup analysis, the correlations between FGF-23 levels and isovolumic relaxation time (ms) and early diastolic velocity at medial/septal annulus (E'med) (m/s) were significant only in patients with early diabetic nephropathy (DN) but not in non-DN patients. No significant association of sKlotho levels with echocardiographic findings was noted. Our findings in young adult type 1 diabetic patients with GFR > 60 ml/min versus healthy controls revealed no difference between groups in terms of sKlotho and FGF-23 levels and echocardiographic findings, while a significant correlation of FGF-23 (pg/ml) levels and diastolic dysfunction was noted only in patients with DN.
Keywords: Type 1 diabetes mellitus; sKlotho; FGF-23; Cardiac function; Diabetic nephropathy; CHRONIC KIDNEY-DISEASE; LEFT-VENTRICULAR HYPERTROPHY; SOLUBLE SERUM KLOTHO; HEART-FAILURE; CARDIOVASCULAR-DISEASE; VASCULAR DYSFUNCTION; FGF-23; MORTALITY; PHOSPHATE; COMMUNITY